The effect of treating obstructive sleep apnea with positive airway pressure on depression and other subjective symptoms: A systematic review and meta-analysis. (August 2016) - Gupta, Madhulika A.; Simpson, Fiona C.; Lyons, Danika C.A.
Summary: Patients with obstructive sleep apnea (OSA) frequently present with symptoms of depression and anxiety. The objective of this study is to determine if treatment with positive airway pressure (PAP) improves symptoms of depression and anxiety. A systematic review was conducted to identify clinical trials of PAP that contained a validated measure of depression severity. Meta-analysis was conducted for depression, anxiety, excessive daytime sleepiness (EDS), quality of life (QoL) and respiratory variables. The systematic review included 33 reports. Pre-post-test analysis of PAP showed a moderate effect size (Hedge's g, 95% CI) for depression 0.524 [0.401–0.647], but a low effect size compared to oral placebo (0.355 [0.187–0.524]) and no effect when compared to dental appliances (0.107 [−0.72–0.287]) and sham PAP (−0.049 [−0.292–0.194]). Anxiety, EDS, and QoL showed similar improvement in pre-post-test analysis, but a lack of superiority to dental appliances and sham PAP. PAP was superior to all comparators for respiratory variables. PAP has a moderate clinical effect on symptoms of depression and anxiety in OSA, but it is not superior to dental appliances or sham PAP. The improvement in subjective symptoms, such as depression and anxiety, may be mediated by patient expectations and contact with healthcare providers.